The Influence of the Team-Based Learning Model on Students’ Procedural Knowledge Learning Outcomes in Information and Communication Technology Subjects - Siti Rofiqoh; Etistika Yuni Wijaya; Puji Rahayu Ningsih; Laili Cahyani; Luluk Mauli Diana (invotek, 2024)
Improving students' learning outcomes in terms of procedural knowledge in the subject of Information and Communication Technology (ICT) remains a significant challenge in the field of education. This is due to the limitations of traditional teaching methods, which are less effective in promoting active student engagement and are not optimal in developing critical thinking and problem-solving skills. To address this issue, this study aims to explore the implementation of the Team-Based Learning (TBL) model as an innovative instructional strategy that focuses on teamwork and active participation in the learning process. The TBL model is designed to enhance both conceptual understanding and procedural skills through group discussions, individual and team quizzes, and real-world applications. This study employs a quasi-experimental design involving two groups: an experimental group that applies the TBL model and a control group that uses conventional teaching methods. The results indicate that the implementation of TBL significantly improves students' procedural knowledge, encourages active interaction between teachers and students, and receives positive feedback from learners. These findings highlight the great potential of TBL as an effective approach to improving the quality of ICT learning in schools.